2021
DOI: 10.3389/fvets.2021.674730
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Data Mining of Rapid Residue Detection Assay Data From HTML and PDF Documents: Improving Data Access and Visualization for Veterinarians

Abstract: Extra-label drug use in food animal medicine is authorized by the US Animal Medicinal Drug Use Clarification Act (AMDUCA), and estimated withdrawal intervals are based on published scientific pharmacokinetic data. Occasionally there is a paucity of scientific data on which to base a withdrawal interval or a large number of animals being treated, driving the need to test for drug residues. Rapid assay commercial farm-side tests are essential for monitoring drug residues in animal products to protect human healt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We used VOSviewer software to analyze the association between the most productive authors and the most cited references to generate the network map and clusters visualization. Finally, we augmented qualitative text analysis using natural language processing (NLP) to investigate key characteristics and the pattern associations with nanotechnology and the top 10 cancer types [30,31]. Under the qualitative method, we mainly focus on qualitative text analysis or qualitative content analysis (e.g., thematic analysis).…”
Section: Methodsmentioning
confidence: 99%
“…We used VOSviewer software to analyze the association between the most productive authors and the most cited references to generate the network map and clusters visualization. Finally, we augmented qualitative text analysis using natural language processing (NLP) to investigate key characteristics and the pattern associations with nanotechnology and the top 10 cancer types [30,31]. Under the qualitative method, we mainly focus on qualitative text analysis or qualitative content analysis (e.g., thematic analysis).…”
Section: Methodsmentioning
confidence: 99%
“…Data acquisition was a critical step in constructing our tool registry. The current commonly used PDF table batch-extraction tools for extracting structured data from the literature are Tabula ( https://github.com/tabulapdf/tabula ) and Camelot ( https://github.com/camelot-dev/camelot ), which have been used for table extraction [ 59 , 60 ]. However, for some PDF documents, these tools do not perform very well.…”
Section: Discussionmentioning
confidence: 99%
“…These show the impact of these mining paradigms in healthcare applications where text or data mining provides useful information [ 62 , 65 , 66 , 67 ]. These studies are found in scientific literature, social media resources, and pharmacovigilance sources, for instance, provided by the US Food and Drug Administration (FDA) [ 47 , 68 , 69 , 70 ]. In a sense, these studies contribute to the establishment of an evidence-based drug safety protocol.…”
Section: Discussionmentioning
confidence: 99%